Mediation as Problem-Solving Scene in the Light of PTC - Viktor Németh (KOME: An International Journal of Pure Communication Inquiry, 2014)
Mediation does not only mean a specific procedure or protocol but the related attitude, mindset as well. This perspective gives opportunity to demonstrate the problem in a different way than previously. In the present study, the Participatory Theory of Communication (PTC) appears as a framework which makes the communication of participants of the mediation interpretable and transparent.